Jim Crow wisdom : memory and identity in Black America since 1940 - Holloway, Jonathan Scott (The University of North Carolina Press, 2013)
How do we balance the desire for tales of exceptional accomplishment with the need for painful doses of reality? How hard do we work to remember our past - or to forget it? These are some of the questions that the author addresses in this exploration of race memory from the dawn of the modern civil rights era to the twenty-first century. Relying on social science, documentary film, dance, popular literature, museums, memoir, and the tourism trade, the author explores the stories Black Americans have told about their past and why these stories are vital to understanding a modern Black identity. In the process, the author asks much larger questions about the value of history and facts when memories do violence to both. Making discoveries about his own past while researching this book, the author weaves first-person and family memories into the traditional third-person historian's perspective. The result is a highly readable, rich, and deeply personal narrative that will be familiar to some, shocking to others, and thought-provoking to all readers. --